Income redistribution in the world of inequality - Krajewska, Anna; Krajewski, Piotr; Piłat, Katarzyna (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
For many years, discussions of changes in the Polish economy have focused primarily on economic growth and relatively little attention has been paid to the growing income inequality. However, the growth of interest in the world literature in the problem of inequality and the increase in income inequality in Poland have prompted attention to ways of counteracting this phenomenon against the background of the experience of other European Union countries. For this reason, the book analyses income inequality in the European Union, with a special focus on the Polish economy, and shows the mechanisms through which redistribution affects the reduction of income inequality in modern economies. The analysis carried out in the book shows that income redistribution taking place through taxes and public spending can be an effective tool for reducing income inequality in the countries of the European Union. At the same time, based on the international comparisons, it can be observed that these instruments have been used to an unequal extent in different models of social policy. In particular, the analyses indicate that taxes have an insufficient effect on income redistribution in Poland. Therefore, in order to more effectively reduce income inequality in the Polish economy, a significant reform of the tax system is recommended, including, among other, an increase in the share of income and property tax revenues in budget revenues, or unification of the rules on the use of progressivity in income taxes.